2014
DOI: 10.3164/jcbn.14-11
|View full text |Cite
|
Sign up to set email alerts
|

Dietary combination of sucrose and linoleic acid causes skeletal muscle metabolic abnormalities in Zucker fatty rats through specific modification of fatty acid composition

Abstract: A dietary combination of sucrose and linoleic acid strongly contributes to the development of metabolic disorders in Zucker fatty rats. However, the underlying mechanisms of the metabolic disorders are poorly understood. We hypothesized that the metabolic disorders were triggered at a stage earlier than the 8 weeks we had previously reported. In this study, we investigated early molecular events induced by the sucrose and linoleic acid diet in Zucker fatty rats by comparison with other combinations of carbohyd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 42 publications
(47 reference statements)
0
10
1
Order By: Relevance
“…Metabolic dysfunctions associated with alterations in the expression of endoplasmic reticulum stress-inducible genes (e.g. binding immunoglobulin protein, C/EBP homologous protein and X-box binding protein 1) are aggravated by high consumption of linoleic acid and, consequently, increased content of arachidonic acid in soleus muscle (Ohminami et al 2014). These authors also reported that dietary linoleic acid itself promotes inflammation through c-Jun NH 2 -terminal kinase activation in soleus muscle.…”
Section: P Abreu and Othersmentioning
confidence: 96%
See 2 more Smart Citations
“…Metabolic dysfunctions associated with alterations in the expression of endoplasmic reticulum stress-inducible genes (e.g. binding immunoglobulin protein, C/EBP homologous protein and X-box binding protein 1) are aggravated by high consumption of linoleic acid and, consequently, increased content of arachidonic acid in soleus muscle (Ohminami et al 2014). These authors also reported that dietary linoleic acid itself promotes inflammation through c-Jun NH 2 -terminal kinase activation in soleus muscle.…”
Section: P Abreu and Othersmentioning
confidence: 96%
“…Treatment with linoleic acid increased the content of eicosadienoic acid (20:2, n−6) and arachidonic acid (20:4, n−6) in gastrocnemius muscle, suggesting an increase in 6 desaturase activity (Jung et al 2010;Shin et al 2012;Ohminami et al 2014;Reinders et al 2015). binding immunoglobulin protein, C/EBP homologous protein and X-box binding protein 1) are aggravated by high consumption of linoleic acid and, consequently, increased content of arachidonic acid in soleus muscle (Ohminami et al 2014). Accordingly, dietary supplementation with linoleic acid leads to an increase of arachidonic acid content in the tissues (Soriguer et al 2000).…”
Section: P Abreu and Othersmentioning
confidence: 99%
See 1 more Smart Citation
“…Only one previous study has quantified the effect of ISO treatment on muscle-specific glucose uptake. ( 9 ) In that report, the authors measured insulin-stimulated glucose uptake in vivo in soleus and gastrocnemius muscles from the rats treated ISO for 4 weeks, but observed no significant difference when the measurement was made following a 12-h fasting period after the end of treatment. Notably in this regard, a previous study by our group provided evidence that 24-h-lasting fasting amplified insulin-stimulated glucose uptake in comparison with the fed condition, ( 13 ) demonstrating that short-term fasting has an insulin-sensitizing effect on skeletal muscle.…”
Section: Discussionmentioning
confidence: 94%
“…Indeed, several studies have demonstrated that chronic ISO treatment attenuates accumulation of visceral fat. ( 6 8 , 10 ) However, ISO treatment has a positive effect on peripheral insulin action even in non-obese and non-insulin-resistant subjects, ( 5 ) as well as in insulin-resistant rats, without reduction of visceral fat mass, ( 9 ) indicating that ISO treatment could have an impact on muscle insulin action independently of reduction in visceral fat mass as observed after chronic ISO treatment (several weeks or more). Accordingly, we hypothesized here that short-term ISO treatment, in the absence of changes in fat mass, could enhance muscle insulin action, and that ISO might exert this effect via responses occurred in skeletal muscle itself, rather than through secondary effects in other tissues.…”
Section: Introductionmentioning
confidence: 99%